Developing Pattern Regional Plan on Adaptation to Climate Change - N. I. Dorogov; N. S. Kulyasov; E. V. Kulyasova (Вестник Российского экономического университета имени Г. В. Плеханова)
The article analyzes CO2 emissions in the world and in Russia. Retrospective analysis of regulatory and legal framework and key steps aimed at preventing climate change in Russia was carried out. Economic and administrative tools of cutting greenhouse gas emissions were studied. The author’s approach to shaping the structure of a pattern regional plan on adaptation to climate change was put forward. The author came to grounded conclusions that key measures aimed at higher efficiency of carbon regulation in Russia shall include elaboration and implementation of regional plans on adaptation to climate change in entities of the Russian Federation. The developed pattern regional plan can be used in practical work of executive power bodies to shape regional plans and to appraise results of measures aimed at adaptation to climate change. It can be important for identifying steps, which could cut emissions, prevent ecological and economic damage and at the same time provide a positive impact on enterprise work, working conditions and people standard of life.